Moominpappa's memoirs - Jansson, Tove (Farrar, Straus, Giroux, 2010)
When stricken with a severe cold, Moominpappa decides to set down an account of his eventful youth, which he shares chapter by chapter with Moomintroll, Sniff, and Snufkin.